(untitled) (Journal of Geography and Environmental Management, 2024)
All over the world, agriculture will have to adapt to new climatic conditions. Experts from the International Food Organization have concluded that after 2030, crop yields will decrease in many regions of the world due to climate change. For agriculture, the greatest danger is posed by such manifestations of climate change as rising temperatures, changing precipitation patterns, sea level rise (for coastal lowlands) and frequent droughts and floods, especially in areas prone to natural disasters. These changes are affecting agriculture, and the problem of ensuring food security is becoming more acute. This article discusses the problem of rational use of agricultural land in the Western region of Kazakhstan in the context of climate change. The main focus is on the need to adapt agriculture to new climatic conditions and the efficient use of available land resources. The paper presents the key aspects of this problem, analyzes possible solutions and offers recommendations for the sustainable development of agriculture in the region.